Social Stigma and Crime – Social Analysis - MOURAKEB, Souha; BENKHALED, djamel (Journal of Social Sciences and Humanities, 2023)
Social stigma is the character that the individual is marked regardless of the act committed by him and is one of the phenomena we must put an end to because it is a danger to social structure. This debate addresses the role of social stigma as a factor and cause for creating the criminal and crime within society, stigma is a cruel social punishment that society has inflicted on the individual is the act of exclusion and social rejection, for that we say the stigma is a factor in creating the offender and generating crime and increasing its proportion within societies rather than preventing it.